A Critical Review of Race, Class, and Gender in Adult Development Models and Theory: Implications for Adult Education - Elice E. Rogers (Adult Education Research Conference, 2001)
The purpose of this roundtable is to discuss North American literature showing how race, class, and gender has been treated historically and presents three approaches or perspectives that inform contemporary literature.